The Potential Regulatory Roles of Circular RNAs in Tumor Immunology and Immunotherapy - Fang, Zhixiao; Jiang, Chunjie; Li, Shengli (Frontiers in Immunology, 2021)
Circular RNAs (circRNAs) are covalently closed RNA molecules in eukaryotes with features of high stability, tissue-specific and cell-specific expression. According to their biogenesis, circRNAs are mainly classified into six types, i.e. exonic circRNAs (EciRNAs), exon-intron circRNAs (EIciRNAs), intronic RNAs (CiRNAs), fusion circRNAs (f-circRNAs), and read-through circRNAs (rt-circRNAs). CircRNAs have been emerging as important non-coding regulatory RNAs in a variety of human cancers. CircRNAs were revealed to exert regulatory function through multiple mechanisms, such as sponges/decoys of miRNAs and proteins, enhancers of protein functions, protein scaffolds, proteins recruitment, or protein translation templates. Furthermore, some circRNAs are intensively associated with immune cells in tumor immune microenvironment (TIME), e.g. circARSP91 and natural killer cells. Through regulating immune checkpoint genes, circRNAs are demonstrated to modulate the immune checkpoint blockade immunotherapy, e.g. circCPA4 could up-regulate PD-L1 expression. Advances in high-throughput sequencing technologies and computational algorithms will drive deeper exploration of circRNAs regulatory roles in tumor immunology and immunotherapy. Further understanding of the regulatory roles of circRNAs in tumor immunology and immunotherapy will benefit tumor treatment.